STUDENTS’ MOTIVATION TO PARTICIPATE IN AN ENGLISH SPEECH COMPETITION AT STAIN BATUSANGKAR - Saputra, Riyadi (RC-INSTITUT, 2017)
This research is based on students’ motivation to participate an English speech competition. This research aims at knowing students’ motivation to participate an English speech competition II at STAIN Batusangkat in 2011/2012 academic year. This research is a qualitative research which describes students’ motivation to participate an English speech competition II at STAIN Batusangkar. Informants in this research were all students that participated an English speech competition II that consisted 25 participants trough snowball sampling. Instrument used in this research was interview. Interview was used to get the data about students’ motivation to participate an English speech competition II that registered in 2011/2012 academic year. Result of this research shows that there two kinds of motivation that students participate an English speech competition; intrinsic and extrinsic motivation. Intrinsic motivation is divided into 6 types, namely: 1) the need for self-confidence to speak in public; 2) the need for practicing English in order to improve English and to pronounce English well; 3) the need for measuring English speaking ability compete to others participants; 4) the need for showing that non-English students are able to speak English; 5) the need for happiness that can be participant an English speech competition; 6) the need for having relationship with other participants. Furthermore, extrinsic motivation can be divided into 5 types, namely: 1) the need for getting rewards; 2) the need for supporting by others; 3) the need for a test; 4) the need for winning and competing other participants; 5) the need for getting experience. Dealing with students’ motivation above, it can be said that “the need for self-confidence to speak in public” is the most dominant (30.8 %) of students’ motivation to participate the English speech competition.